The rise of smart cities advanced structural sensing and monitoring systems - Alavi, Amir H. (Butterworth-Heinemann, 2022)
The Rise of Smart Cities: Advanced Structural Sensing and Monitoring Systems provide engineers and researchers with a guide to the latest breakthroughs in the deployment of smart monitoring technologies over the past three decades. The book introduces research engineers and engineering designers to the latest innovations in the area of advanced structural sensing systems and how they can be integrated into the planning and design of smart cities. Topics include complementary technological paradigms such as machine learning, big data analytics, cloud computing and Internet of Things (IoT) With this book in hand, researchers and design engineers will find a valuable reference in terms of civil infrastructure health monitoring, advanced computation, data mining, data fusion, and state-of-the-art nondestructive testing and evaluation (NDT&E) techniques.